Correspondência fazer-dizer em adultos: o controle pela audiência em um jogo virtual - Alves, Cristiane (2018)
Studying the relationship between what is done and what is said has occurred in several sciences, including Behavior Analysis. The present study employed do-say sequence and examined, experimentally, the effect of the audience on the phenomenon of correspondence in self-report in adults. The first stage of this thesis consisted in the elaboration, production and testing of a 3D virtual game with the function of an instrument for data collection. The next step was data collection and analysis. Ten male college students were submitted to the game. The experimental task consisted in collecting red and green objects in the game scenario and reporting "yes/no", if they collected the reds that were prohibited. Audiences were established through the characters of the game, one of which indicated only punishment, another only reinforcement and another signalized, in an ambiguous way, both punishment and reinforcement. After the game, the participants evaluated, through a questionnaire, the game and the characters, with the objective to check if they responded adequately to the programmed characterization for the audiences. The results indicated a higher frequency of distorted reports for the audiences that indicated punishment or ambiguity between punishment and reinforcement. This indicates that the audience had an effect on the accuracy of verbal reports of adults in a virtual environment.